Demonstration of Cerebral Venous Variations in the Region of the Third Ventricle on Phase-Sensitive Imaging - Fujii, S.; Kanasaki, Y.; Matsusue, E.; Kakite, S.; Kminou, T.; Ogawa, T. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Susceptibility-weighted (SW) MR imaging has enabled noninvasive visualization of the cerebral veins and has shed light on the nature of venous architecture. For successful surgery of the third ventricle, understanding of the anatomy of the subependymal veins of the lateral ventricle and their relationships to the foramen of Monro is required preoperatively. The purpose of this study was to evaluate the anatomic variations of the subependymal veins around the third ventricle by use of phase-sensitive imaging (PSI) on the basis of principles similar to those of SW MR imaging. MATERIALS AND METHODS: Included in this study were 642 sides in 321 patients. The courses of the anterior septal vein (ASV), thalamostriate vein, and internal cerebral vein (ICV) were evaluated. We classified these into 4 types (IA, IB, IIA, IIB) on the basis of standard classic angiographic criteria. The classification is based on their relationship with the ASV-ICV junction and the presence of a venous angle or a false venous angle, according to the method in a previous study. Other venous variations were classified as type III. RESULTS: A venous angle was formed in 519 (80.9%), whereas a false venous angle was formed in 123 (19.1%). The ASV-ICV junction was located at the venous angle (type IA) in 407 (63.4%) of 642 sides. In 235 sides (36.6%), the ASV-ICV junction was located posteriorly beyond the foramen of Monro (types IB, IIA, IIB, and III). CONCLUSIONS: PSI is useful for understanding normal variations of the subependymal veins in the region of the third ventricle.